Substitution of The Laor Worm (Polychaeta) Flour on Nutritional Content and Organoleptic Properties of Laor Sago Crackers - Siahaya, Griennasty Clawdya; Rehena, Zasendy (Agrikan Jurnal Agribisnis Perikanan, 2022)
The purpose of this study was to determine the effect of substitution of laor worm flour on the nutritional content (carbohydrates, protein, fat) of sago crackers. The research method used in this study is an experimental study using a one-factor Completely Randomized Design design, namely the substitution of laor worm flour in the formulation of sago laor crackers with a concentration of 0% (TCL 0); 2,5% (TCL 1); 5 % (TCL2); 7.5% (TCL3) with 3 replicates. The results showed that there was an effect of substitution of laor worm flour on the nutritional content of carbohydrates (significant 0.00 < 0.05), protein content (significant 0,00 < 0,05) and fat content (significant 0,00 < 0,05) sago laor crackers. Based on the results of the organoleptic test, it was found that the sago crackers with 7.5% laor worm flour (TCL3) were highly favored by the panelists for the aroma, taste and texture criteria with a very favorable rating, while the color was indicated by the criterion of liking compared to the other three treatments, namely TCL0, TCL1 and TCL2. Based on the research that has been done, further research needs to be done including analyzing the nutritional value for the energy content of crackers, the shelf life of cracker products and product packaging so that the results can be empowered by the community.